Musical worlds in Yogyakarta - Richter, Max M. (Institute of Southeast Asian Studies, 2013)
Musical Worlds in Yogyakarta is an ethnographic account of a vibrant Indonesian city during the turbulent early post-Soeharto years. The book examines musical performance in public contexts ranging from the street and neighbourhood through to commercial venues and state environments such as Yogyakarta's regional parliament, its military institutions, universities and the Sultan's palace. It focuses on the musical tastes and practices of street workers, artists, students and others. From street-corner jam sessions to large-scale concerts, a range of genres emerge that cohere around notions of campursari ("mixed essences") and jalanan ("of the street"). Musical worlds addresses themes of social identity and power, counterpoising Pierre Bourdieu's theories on class, gender and nation with the author's alternative perspectives of inter-group social capital, physicality and grounded cosmopolitanism. The author argues that Yogyakarta is exemplary of how everyday people make use of music to negotiate issues of power and at the same time promote peace and intergroup appreciation in culturally diverse inner-city settings